Kepastian Hukum Terhadap Akta Hak Tanggungan Atas Harta Bersama Yang Belum Dibagi Paska Perceraian Tanpa Persetujuan Mantan Suami/Istri - Janthy Prisilya Karundeng; Jelly Nasseri; Felicitas Sri Marniati (JOURNAL of LEGAL RESEARCH, 2022)
In the banking industry, it is a well-known fact that there are frequently issues with joint assets that have not been divided after a divorce and that are used as collateral for mortgage rights. The case of court decision number 177/Pdt. G/2019/PN Bks is illustrative. In this study, the problem to be addressed is the legal consequences of the deed of mortgage on shared assets that have not been divided post-divorce without the ex-husband/consent wife's and the legal certainty of the deed of mortgage on shared assets that have not been divided post-divorce without the ex-husband/consent, wife's using Soeroso's theory of legal consequences and Jan Michelle Otto's Legal Certainty theory. In this work, the author employs a normative legal methodology supported by an empirical methodology. The results of the study indicate that the legal consequences of the mortgage deed on joint assets that have not been divided after the divorce without the consent of the ex-husband or ex-wife can result in the mortgage being made and a cancellation lawsuit being filed because it violates the ex-rights. spouse's Based on Jan Michel Otto's legal certainty theory, a mortgage deed formed on joint assets that have not been divided after divorce without the approval of the ex-husband/wife has no legal certainty value because the mortgage is made without the consent of the ex-husband/wife.